2010
DOI: 10.1021/ja1084207
|View full text |Cite
|
Sign up to set email alerts
|

Protodeboronation of Tertiary Boronic Esters: Asymmetric Synthesis of Tertiary Alkyl Stereogenic Centers

Abstract: While tertiary boranes undergo efficient protodeboronation with carboxylic acids, tertiary boronic esters do not. Instead, we have discovered that CsF with 1.1 equiv of H2O (on tertiary diarylalkyl boronic esters) or TBAF·3H2O (on tertiary aryldialkyl boronic esters) effect highly efficient protodeboronation of tertiary boronic esters with essentially complete retention of configuration. Furthermore, substituting D2O for H2O provides ready access to deuterium-labeled enantioenriched tertiary alkanes. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 217 publications
(130 citation statements)
references
References 52 publications
7
123
0
Order By: Relevance
“…Treatment of this ester with carboxylic acids at elevated temperatures, as reported by Brown and Murray for the protodeboronation of boranes 15 , was ineffective, as was the use of TBAF·3H 2 O, a reagent that we had employed for the protodeboronation of reactive benzylic and allylic pinacol boronic esters 9,16 . We therefore considered the protonation of the more-reactive boronate complex formed from the addition of p-MeOPhLi (6a) because such species were found to be reactive nucleophiles 17 .…”
Section: Resultsmentioning
confidence: 94%
“…Treatment of this ester with carboxylic acids at elevated temperatures, as reported by Brown and Murray for the protodeboronation of boranes 15 , was ineffective, as was the use of TBAF·3H 2 O, a reagent that we had employed for the protodeboronation of reactive benzylic and allylic pinacol boronic esters 9,16 . We therefore considered the protonation of the more-reactive boronate complex formed from the addition of p-MeOPhLi (6a) because such species were found to be reactive nucleophiles 17 .…”
Section: Resultsmentioning
confidence: 94%
“…was possible, but with only moderate enantiospecificity (primary boronic ester 39 was obtained in 88 : 12 e.r.). 27 The group of Morken has shown that primary boronic esters can be transformed selectively in the presence of a vicinally-positioned secondary boronic ester under Suzuki cross-coupling conditions. 3 b However, although facile cross coupling of the primary boronic ester in 15 was evident, the conditions were also favourable for protodeboronation of the tertiary boronic ester, giving 1,2-diarylpropane 40 in 75% yield.…”
Section: Resultsmentioning
confidence: 99%
“…No deborylation was observed when the substrates in entries 2 and 5 were subjected to Perrin’s and Aggarwal’s conditions, respectively. 8,9 …”
Section: Resultsmentioning
confidence: 99%
“…For example, benzylic organoboronates undergo stereo-specific proto- and deuterodeborylations in the presence of CsF and H 2 O/D 2 O. 8 It has also recently been shown that extremely electron-deficient aromatic and heteroaromatic boronic acids can be selectively deborylated in 0.2 M hydroxide solutions. 9 Alternatively, electron-rich boronic acids can be deborylated using water or acetic acid as the proton source.…”
Section: Introductionmentioning
confidence: 99%